Development of STEM-Based Interactive Multimedia as an Effort to Increase Student Learning Motivation in Biology Learning - Basri, Rafyka; Adlini, Miza Nina (Jurnal Pendidikan MIPA, 2023)
This study aims to develop a interactive multimedia based on STEM that was valid, practical and effective, to able improve motivation Students in biology learning. The study employs the method of research and development. The research model is model 4D (define, design, development, and dissemination). Based on validity test, the interactive multimedia based on STEM was categorized as very valid with 95,6 % by a materials expert and was categorized as very valid with 85% by a media expert. Based on practicality test, the interactive multimedia practically used with 77 % practicality level by educators response and verry practically with 77, 94% by students response. Based the questionnaire motivation students was very effective with 79,07%. From these result, the develop interactive multimedia was very valid, very practical, and very effective to improve motivation learners in biology learningKeywords: stem, interactive multimedia, motivation, biology learningDOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp384-392